2021
DOI: 10.1016/j.ijid.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of commercial automated SARS-CoV-2 immunoassays

Abstract: Highlights FDA-EUA approved anti-SARS-CoV-2 tests compare favorably with others. longitudinal patterns of antibody development are subject to high individual variability. comparing the assays of leading manufacturers, there are considerable differences in terms of achieved and stated sensitivity/specificity. Immune response relies on disease severity, thus need to be considered for validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In general, the sensitivity of the comparator assays tested in the present study is consistent with previous findings [ 35 39 ]. The low sensitivity of the iFlash SARS-CoV-2 IgM assay in the present study is in accordance with that previously reported [ 40 ]. A potential explanation for this is the fact that detection of SARS-CoV-2-specific IgM is limited to very early on in the infection cascade; only 20% of SARS-CoV-2 infected individuals present IgM before IgG, and the majority will present both IgM and IgG in tandem [ 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…In general, the sensitivity of the comparator assays tested in the present study is consistent with previous findings [ 35 39 ]. The low sensitivity of the iFlash SARS-CoV-2 IgM assay in the present study is in accordance with that previously reported [ 40 ]. A potential explanation for this is the fact that detection of SARS-CoV-2-specific IgM is limited to very early on in the infection cascade; only 20% of SARS-CoV-2 infected individuals present IgM before IgG, and the majority will present both IgM and IgG in tandem [ 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…Parai et al reported sensitivity and specificity values of 76.9% and 100%, respectively, for the iFlash-SARS-CoV-2 IgG kit 12 . Kittel et al also reported sensitivity and specificity values of 77% and 100%, respectively, for the iFlash-SARS-CoV-2 IgG kit 13 . The sensitivity of the iFlash-SARS-CoV-2 IgG-S1 kit was 19.7% for RT-PCR-positive patients 1 to 7 days after symptom onset, 67.6% for RT-PCR-positive patients 8 to 14 days after symptom onset and 98.3% for RT-PCRpositive patients ≥15 days after symptom onset, and the specificity of the iFlash-SARS-CoV-2 IgG-S1 kit was 100% for RT-PCR-negative samples (Supplementary Fig.…”
Section: Measurement Of Anti-sars-cov-2 Antibody Levelsmentioning
confidence: 97%
“…This study is a systematic review and meta-analysis of published articles about the diagnostic accuracy of COVID-19 antibody tests namely Enzyme-Linked Immunosorbent Assay (ELISA), Chemiluminescence Immunoassay (CLIA), and Lateral Flow Immunoassay (LFIA) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the researchers excluded three (3) articles that did not provide absolute data for specificity and sensitivity and another three (3) articles that did not use the gold standard RT-PCR to diagnose COVID-19. After keen assessment and screening done by the researchers, a total of nineteen (19) journal articles [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] were found appropriate to be included in this systematic review and quantitative or meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation